"A study on market potential for Giant private brand" a case study in Giant Hypermarket Bandar Kinrara, Puchong Selangor / Fadhilah Yutiman (Faculty of Business and Management, 2007)
In Malaysia, the name Giant has become synonymous with everyday low prices, big variety and great value. This has been underscored by the Shoppers Trend Survey, which showed that Giant was perceived as the cheapest place, in Malaysia, to shop for everyday groceries. Owned by GCH Retail Sdn Bhd, Giant is a 50-year old Malaysian brand built on its ability to deliver low prices everyday to consumers. It started by the Teng family as a simple grocery store in one of the suburbs of Kuala Lumpur in 1944. Its mission was to offer a wide variety of products at the lowest possible prices. As its reputation grew, so did its business. GCH Retail Sdn Bhd, which acquired Giant in 1999, recognized that the key to Giant's success had been its ability to continuously offer value for money. This core principle had been retained even as it began transforming Giant into a national and international brand.